1999
DOI: 10.1111/j.1528-1157.1999.tb01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Seizures in Mice Lacking Cellular Prion Protein

Abstract: Summary:Purpose: The physiologic role of the cellular prion protein (PrP') is unknown. Mice devoid of PrPC develop normally and show only minor deficits. However, electrophysiologic and histologic alterations found in these mice suggest a possible role for PrP" in seizure threshold andor epilepsy.Methods: We tested the sensitivity of PrP" knockout mice to seizures induced by single convulsant or repeated subconvulsant (kindling) doses of pentylenetetrazol (PTZ), and to status epilepticus (SE) induced by kainic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
116
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 13 publications
13
116
3
2
Order By: Relevance
“…Current evidence suggests that the mechanism underlying the neuroprotective properties of PrP c involves a copper-binding activity that protects cells from oxidative damage (Brown et al, 1997a(Brown et al, , 2002. In support of this hypothesis, cerebellar cell cultures from PrP c null mice are more susceptible to oxidative stress than wild-type mice (Brown et al, 1997b), and PrP c null mice are more susceptible to acute seizures and kindling induced by different protocols than their wild-type counterparts (Walz et al, 1999). Such a neuroprotective function may indicate a possible reason why we observed PrP c to be highly upregulated in the dentate gyrus after TBI in this study.…”
supporting
confidence: 57%
“…Current evidence suggests that the mechanism underlying the neuroprotective properties of PrP c involves a copper-binding activity that protects cells from oxidative damage (Brown et al, 1997a(Brown et al, , 2002. In support of this hypothesis, cerebellar cell cultures from PrP c null mice are more susceptible to oxidative stress than wild-type mice (Brown et al, 1997b), and PrP c null mice are more susceptible to acute seizures and kindling induced by different protocols than their wild-type counterparts (Walz et al, 1999). Such a neuroprotective function may indicate a possible reason why we observed PrP c to be highly upregulated in the dentate gyrus after TBI in this study.…”
supporting
confidence: 57%
“…In addition, both lines showed deficits in synaptic transmission (Collinge et al, 1994;Herms et al, 1995) and increased sensitivity to oxidative stress (Brown et al, 2002). Recent studies indicate that these mice also show increased susceptibility to glutamate excitotoxicity (Khosravani et al, 2008a;Rangel et al, 2007;Walz et al, 1999;Walz et al, 2002) as a result of changes in the expression of glutamate receptor subunits (Khosravani et al, 2008a;Lledo et al, 1996;Rangel et al, 2007). More recently, a conditional knockout of PrP c has been generated (Mallucci et al, 2002).…”
Section: Prnp-deficient Micementioning
confidence: 99%
“…For example, deletion of PrP C increased neuronal predisposition to damage by modulating susceptibility to apoptosis 9,10 and the negative consequences of oxidative stress. [11][12][13] Furthermore, in vivo studies demonstrated that PrP C -deficient mice were more prone to seizure induction, 14 and exhibited an increased extent of cerebral damage following an ischemic challenge. 15 In contrast, adenovirus-mediated PrP C overexpression reduced CNS damage in a rat model of cerebral ischemia.…”
mentioning
confidence: 99%